Employee Performance in a Tourism Organization: The Roles of Training, Discipline, and Work Climate - Nisa Nur Komariah; Hima Barima (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Employee performance is a critical issue in tourism service organizations because it directly affects service quality, visitor experience, and operational reliability. This study examines the effects of job training, work discipline, and work climate on employee performance at Owabong Waterpark Purbalingga, Indonesia. Grounded in the Ability–Motivation–Opportunity (AMO) framework, job training is positioned as an ability-enhancing factor, work discipline as a behavioral regulation aspect of motivation, and work climate as an opportunity-enhancing factor. A quantitative explanatory design was employed using a cross-sectional survey of 131 employees. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results show that job training, work discipline, and work climate positively and significantly affect employee performance. Work discipline has the strongest effect, indicating the importance of punctuality, responsibility, attendance, and procedural compliance in waterpark operations. The model explains 79.5% of the variance in employee performance. This study extends the AMO framework to an attraction-based regional tourism context and provides practical guidance for improving employee performance through training, discipline reinforcement, and a supportive work climate.